PENINGKATAN KEMAMPUAN MENULIS NASKAH DRAMA SATU BABAK MENGGUNAKAN METODE NUMBERED HEAD TOGETHER TAHUN PELAJARAN 2018/2019 - Martina Septiani Sirait; Panigoran Siburian; Syahrizal Akbar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This research aims at finding the process and result quality and describing the improvement of writing ability of drama text for students of SMP N 3 PancurBatu. It is classroom action research conducted for second year studentsof SMPN 3 PancurBatu. Cycle I and cycle II consists of planning, observing, and reflecting. The variable of this research is the ability in writing one chapter drama text in which the method used is Number Head Together. Technique of collecting data was done by observation, interview, and documentation. Based on test in cycle I and II, learning of writing a one-round drama script with the Numbered Head Together method on second-year student is significant. Completeness of learning outcomes is 66.67% or as many as 20 students are completed. Meanwhile, on cycle II it was got 76.67% or 23 students are completed. Based on research result, it can be summarized that the use of Numbered Head Together method can improve the students’ ability in writing a one-round drama script